2015
DOI: 10.1093/cid/civ154
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Computed Tomography Angiography Improves the Radiographic Diagnosis of Invasive Mold Disease in Patients With Hematological Malignancies

Abstract: Vessel occlusion detected by CTPA is a more sensitive and possibly more specific radiographic sign vs other common CT findings of invasive mold disease in patients with hematological malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 23 publications
(35 reference statements)
1
61
1
1
Order By: Relevance
“…Of interest, all the four patients submitted to CTPA for macronodular consolidations revealed no evidence of angioinvasion at initial clinical presentation. This lack of angioinvasion contrasts with our control group with proven IA or mucormycosis in whom CTPA showed vessel occlusion (100% of readable cases) (Fig. ).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Of interest, all the four patients submitted to CTPA for macronodular consolidations revealed no evidence of angioinvasion at initial clinical presentation. This lack of angioinvasion contrasts with our control group with proven IA or mucormycosis in whom CTPA showed vessel occlusion (100% of readable cases) (Fig. ).…”
Section: Discussioncontrasting
confidence: 68%
“…High‐resolution computed tomography (HRCT) of pulmonary IMD could reveal indirect signs of angioinvasion (halo sign, air crescent sign). Recently, computed tomography pulmonary angiography (CTPA) showed to be more sensitive and possibly specific tool for detection of angioinvasion . The reversed‐halo sign is highly suggestive for mucormycosis, but no further radiological findings can discriminate between infections sustained by different moulds.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that CT angiography may be more sensitive than conventional CT in detecting fungal pneumonia in HM/HSCT patients 60 , but is not standard practice. FDG-PET/CT cannot reliably differentiate malignancy from infectious pulmonary nodules.…”
Section: Diagnosis Of Hm/hsct Fungal Pneumioniamentioning
confidence: 99%
“…The diagnosis of invasive fusariosis is based on the growth of the fungus in blood culture or from deep tissue biopsy. More recently, radiological features have been proposed that may help distinguish sinopulmonary infections caused by Fusarium from more common moulds such as Aspergillus . The management of invasive fusariosis is complicated by intrinsic resistance of Fusarium species to many classes of antifungal agents.…”
Section: Introductionmentioning
confidence: 99%